2016
DOI: 10.1002/2016gl070863
|View full text |Cite
|
Sign up to set email alerts
|

Geologic influence on groundwater salinity drives large seawater circulation through the continental shelf

Abstract: Observations of offshore freshened groundwater and saline groundwater discharge along continental shelves have important implications for water resources, ecosystem function, and the composition of the ocean, but they cannot be explained by basic theory. We show that these independent observations are linked and result from processes that drive variable‐density groundwater flow through the spatial heterogeneity that is ubiquitous in geologic formations. We use lithologic data to develop geostatistical models t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
104
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(132 citation statements)
references
References 54 publications
11
104
0
Order By: Relevance
“…Freshened groundwater has been detected tens to hundreds of kilometers offshore of coastlines worldwide (Post et al, ), and simulations indicate that this could be common across a range of geologic systems (Michael et al, ). Offshore groundwater resources can potentially be exploited for uses such as drinking, agriculture, and oil recovery (Bakken et al, ; Jiao et al, ; Kwong et al, ; Person et al, ; Ziegler et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Freshened groundwater has been detected tens to hundreds of kilometers offshore of coastlines worldwide (Post et al, ), and simulations indicate that this could be common across a range of geologic systems (Michael et al, ). Offshore groundwater resources can potentially be exploited for uses such as drinking, agriculture, and oil recovery (Bakken et al, ; Jiao et al, ; Kwong et al, ; Person et al, ; Ziegler et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Onshore and offshore groundwater systems connect through the subsurface, and the extent to which one influences the other depends on the geologic structure. Preferential flow paths can enhance connectivity relative to homogeneous aquifers in systems with karst conduits (Evans & Lizarralde, ; Xu et al, ), palaeochannels (Mulligan et al, ), natural faults (Varma & Michael, ), and a range of other heterogeneous geologic settings (Houben et al, ; X. Li et al, ; Michael et al, ). Knight et al () analyzed 27 coastal sites globally and found that widespread losses of offshore freshwater are associated with onshore pumping due to connections between offshore and onshore fresh groundwater reserves.…”
Section: Introductionmentioning
confidence: 99%
“…Terrestrial groundwater discharge, density‐driven flow, tides, and waves are major driving forces affecting SGD and SWI in coastal aquifers (Figure ) [ Burnett et al ., ; Heiss and Michael , ; Li et al ., ; Michael et al ., ; Moore et al ., ; Taniguchi et al ., ; Xin et al ., ]. In early work, it was assumed that SGD could be estimated based on a summation of fluxes driven by these forces independently [ Burnett et al ., ; Li et al ., ; Taniguchi et al ., ], i.e., SGD = Qf+Qc=Qf+Qd+Qt+Qw where Qf and Qc are the inland freshwater input and total circulating seawater flux, respectively; and Qc is given by a linear combination of the density‐driven flow ( Qd), tidally driven flow ( Qt), and wave‐induced flow ( Qw).…”
Section: Introductionmentioning
confidence: 99%
“…Terrestrial groundwater discharge, density-driven flow, tides, and waves are major driving forces affecting SGD and SWI in coastal aquifers (Figure 1) [Burnett et al, 2006;Heiss and Michael, 2014;Li et al, 1999;Michael et al, 2016;Moore et al, 2008;Taniguchi et al, 2002;Xin et al, 2010]. In early work, it was assumed that SGD could be estimated based on a summation of fluxes driven by these forces independently [Burnett et al, 2006;Li et al, 1999;Taniguchi et al, 2002], i.e., above the denser seawater associated with the saltwater wedge (SW).…”
Section: Introductionmentioning
confidence: 99%
“…SGD is a path for groundwater outflow that may have a substantial effect on water budget of coastal aquifers (e.g., Moore, ), as well as coastal water quality (e.g., Johannes, ; Moore, ) and seafloor morphology (e.g., Orange et al, ). Because of its importance, SGD has been a subject of extensive studies either by direct observations (Burnett et al, , ; Cable et al, ; Lambert & Burnett, ; Moore, ; Swarzenski et al, ) and/or modeling (Bokuniewicz, ; Croucher & O'Sullivan, ; Glover, ; McBride & Pfannkuch, ; Michael et al, ; A. J. Smith, ; L. Smith & Zawadzki, ; Wilson, ). The vast majority of these studies focused on shallow, near‐shore SGD, but SGD can occur also in deeper water along the continental shelf (Bratton, ).…”
Section: Introductionmentioning
confidence: 99%